Pengembangan Kompetensi Guru BK: Dampaknya terhadap Pengelolaan Program BK yang Efektif di Sekolah - Palenza, Nabila Rezky; Syukur, Yarmis; N, Neviyarni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of guidance and counseling (GC) teachers’ competencies plays a crucial role in enhancing the effectiveness of school counseling programs. This study examines how competence development including aspects of professionalism, program evaluation, social competence, and service management impacts the successful planning, implementation, and evaluation of GC programs. Using a literature review method, this study analyzes various empirical studies and theoretical perspectives related to GC teacher competencies and the management of counseling services. The results indicate that GC teachers who receive training, supervision, or professional development tend to be more capable of designing counseling programs that align with students’ needs, implementing counseling services more effectively, and conducting systematic evaluation and management of services. Thus, the development of GC teachers’ competencies significantly contributes to the effectiveness of counseling programs in schools.